2021
DOI: 10.1038/s41419-021-03484-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-induced mitophagy is suppressed by the miR-106b-93-25 cluster in a protective manner

Abstract: Increased reactive oxygen species levels in the mitochondrial matrix can induce Parkin-dependent mitophagy, which selectively degrades dysfunctional mitochondria via the autolysosome pathway. Phosphorylated mitofusin-2 (MFN2), a receptor of parkin RBR E3 ubiquitin-protein ligase (Parkin), interacts with Parkin to promote the ubiquitination of mitochondrial proteins; meanwhile, the mitophagy receptors Optineurin (OPTN) and nuclear dot protein 52 (NDP52) are recruited to damaged mitochondria to promote mitophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 55 publications
0
20
1
Order By: Relevance
“…OPTN expression was substantially increased in cells treated with H 2 O 2 compared with untreated control cells. This result is inconsistent with the findings of Zhang et al ( Zhang et al, 2021 ), who found that continuous administration of low concentrations of H 2 O 2 decreases OPTN expression ( Zhang et al, 2021 ); we believe this difference is due to differences in the cell types studied, the concentration of H 2 O 2 and the duration of treatment. We speculate that short-term oxidative stress causes cells to undergo stress, which promotes mitophagy to counteract the damaging stimulus, resulting in elevated OPTN expression, whereas long-term stress causes oxidative and antioxidant dysregulation, resulting in mitophagy failure.…”
Section: Discussioncontrasting
confidence: 99%
“…OPTN expression was substantially increased in cells treated with H 2 O 2 compared with untreated control cells. This result is inconsistent with the findings of Zhang et al ( Zhang et al, 2021 ), who found that continuous administration of low concentrations of H 2 O 2 decreases OPTN expression ( Zhang et al, 2021 ); we believe this difference is due to differences in the cell types studied, the concentration of H 2 O 2 and the duration of treatment. We speculate that short-term oxidative stress causes cells to undergo stress, which promotes mitophagy to counteract the damaging stimulus, resulting in elevated OPTN expression, whereas long-term stress causes oxidative and antioxidant dysregulation, resulting in mitophagy failure.…”
Section: Discussioncontrasting
confidence: 99%
“…A major disadvantage is that the total number of miRNAs that can target Sirt1 and MFN2 is expanding. For example, miR-22, -34a, -9, -29c and -92a, as well as miR-141 can target Sirt1 [ (17,(42)(43)(44), and the results of the present study], while miR-195, -106b, -93 and -20b, as well as miR-141 can target MFN2 [ (45)(46)(47), and the results of the present study]. Specifically, miR-34a, miR-141 and miR-9 may influence Parkinson's disease pathogenic processes by targeting Sirt1 (17).…”
Section: Discussionmentioning
confidence: 79%
“…Another prostate cancer-specific target of miR-93, MFN2, was shown to suppress breast and thyroid cancer progression through AKT signaling [45, 46]. The direct binding of miR-93 to 3’-UTR of MFN2 was also experimentally validated with luciferase reporter assays [47, 48].…”
Section: Discussionmentioning
confidence: 99%